Students’ Civic Engagement Self-Efficacy Varies Across Socioscientific Issues Contexts - Dauer, Jenny M.; Sorensen, Amanda E.; Wilson, Jena (Frontiers in Education, 2021)
In STEM learning focused on science literacy, socioscientific issues instruction is often proposed as a way to bolster students’ civic engagement, however few studies in science education have explicitly examined this connection. We define civic engagement as the work of influencing legitimately public matters using means within the existing political structure. In this work we investigate students’ feelings of self-efficacy for this type of civic engagement in the context of four socioscientific issues (prairie dog conservation, food insecurity, biofuels and water conservation). This study was in the context of a large enrollment introductory science college course, where students used a structured decision-making process to examine alternative policy solutions to complex socioscientific issues. We qualitatively examined students’ response about their perception of the importance of the issue, their self-efficacy in exploring actions they could take to impact the issue, and the effectiveness of those actions. We found that students’ ideas about impact and effectiveness varied across the four different issues contexts due to students’ sense of the issues’ importance and scale. Generally, students’ ideas about actions they could take to impact the issue were narrow and rarely included political actions like voting. We also found post instruction increases in students’ civic engagement attitudes and skills related to social justice, interpersonal and problem-solving skills and political awareness. Finally, we suggest that socioscientific instruction must have an explicit connection to policy-level decisions and reveal how individual actions can influence the societal system. Our course using a structured decision-making process in the context of socioscientific issues is one model to help students make these connections.